Safety and quality of food (rice and wheat) distributed through Public Food Distribution System (PFDS) in Bangladesh: Results from laboratory tests for selected contaminants - Hoque, Mohammad Mainul; Hoffmann, Vivian (International Food Policy Research Institute, 2019)
Food safety is an umbrella term that encompasses many facets of handling, preparation and storage of food to prevent illness and injury. Included under the umbrella are chemical, microphysical and microbiological aspects of food safety. This study was undertaken to enhance food-risk surveillance and guarantee food safety for the beneficiaries of food aid recipients. It involved a comprehensive assessment of grains at storage facilities of the Government of Bangladesh (GoB)’s Public Food Distribution System (PFDS) for potential risks. The following issues were addressed: (1) Whether the quality of the stored grains meets the requisite global standards set for aflatoxins, arsenic, mold and moisture contents; (2) Critical aspects contributing to grain quality loss as well as assessing the magnitude of the problem; and (3) Establishing remedial actions aimed at minimizing quality loss and largely improving food safety in the overall distribution system. For this research, Local Supply Depots (LSDs) were chosen as primary study sites. Essentially, the research combined data generated from laboratory tests conducted on grain samples, as well as data compiled through a nationally representative survey of public warehouses. To avoid representation bias, a systematic random sampling method was used to select the LSDs to be reported in the study. This ensured an impartial assessment in terms of the food security status of the location and operational size. The findings from this study suggests that grain stored in PFDS do not largely contain any major contaminants (aflatoxins, arsenic and mold) at levels exceeding the maximum allowable limits to pose serious threat to public health. Despite that moisture itself is not a contaminant, excessive moisture content as detected in few cases has implication for mold growth in grain if stored for an extended period of time. Finally, the recommendations outlined in this study for remedial actions are aimed at satisfying most of the stringent standards set under the Food Safety Act as well as ensuring high quality in longer term grain storage.